2009
DOI: 10.1093/intimm/dxp033
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine released by dendritic cells polarizes Th2 differentiation

Abstract: A major neurotransmitter dopamine transmits signals via five different seven transmembrane G protein-coupled receptors termed D1-D5. It is now evident that dopamine is released from leukocytes and acts as autocrine or paracrine immune modulator. However, the role of dopamine for dendritic cells (DCs) and T(h) differentiation remains unclear. We herein demonstrate that human monocyte-derived dendritic cells (Mo-DCs) stored dopamine in the secretary vesicles. The storage of dopamine in Mo-DCs was enhanced by for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
157
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(172 citation statements)
references
References 50 publications
8
157
0
7
Order By: Relevance
“…2) suggest an autocrine mechanism of action of this neurotransmitter. These results are in agreement with previous observations that an anti-DA Ab produced positive immunoreactivity in human monocyte-derived DCs (25). Notably, only D5R expression decreased upon LPS-induced DC maturation, suggesting a role for this receptor during DC maturation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2) suggest an autocrine mechanism of action of this neurotransmitter. These results are in agreement with previous observations that an anti-DA Ab produced positive immunoreactivity in human monocyte-derived DCs (25). Notably, only D5R expression decreased upon LPS-induced DC maturation, suggesting a role for this receptor during DC maturation.…”
Section: Discussionsupporting
confidence: 93%
“…In Tregs, endogenous DA signals through D1R/D5R in a paracrine/autocrine manner resulting in the downregulation of Treg function (23). In DCs, recent pharmacological evidence suggests that the antagonism of D1R/D5R expressed on DCs could impair the polarization of naive CD4 + T cells toward the Th17 phenotype (24,25). However, as the D1R/D5R antagonist used in these studies is also an agonist for serotonin receptors (26,27) and serotonin receptors are also expressed on DCs (28), the individual contributions of specific DARs and serotonin receptors in this phenomenon are not clear (24).…”
Section: Endritic Cells (Dcs) Are the Most Efficient Type Of Apcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding expression of DA receptors (DARs) in immune cells, these receptors have been found not only in cells of the innate immune response such as dendritic cells (DCs), NK cells, macrophages/monocytes and granulocytes (19)(20)(21) but also in cells of the adaptive immune response such as B cells, CD8 + T cells, and CD4 + T cells (22)(23)(24)(25)(26)(27)(28)(29)(30). Despite being lesser studied than in human T cells, DARs expression has also been described in murine T cells (26,31).…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 99%
“…Pharmacological evidence obtained from a group of studies performed with human T cells has suggested that among five DARs described so far (D1R-D5R), both type I (D1R and D5R) and type II (D2R, D3R, and D4R) contribute to the regulation of T cell function. In this regard, Nakano et al (27) have suggested that stimulation of type I DARs expressed on human naive CD4 + T cells would contribute to production of Th2 cytokines, whereas Cosentino et al (32) have suggested that stimulation of type I DARs on Tregs would decrease IL-10 and TGF-b production. Sarkar et al (25) have described that D4R stimulation on human T cells promotes quiescence.…”
Section: P Arkinson's Disease (Pd) Is a Neurodegenerative Disordermentioning
confidence: 99%